Auto-fluorescence of cellulose paper with spatial solid phrase dispersion-induced fluorescence enhancement behavior for three heavy metal ions detection. (30th September 2022) - Qin, Xiaoxiao; Zhang, Zhong; Yang, Tian; Yuan, Li; Guo, Yurong; Yang, Xingbin
Highlights: The auto-fluorescence of cellulose is explored as a response fluorescence. The lignosulfonate is primarily speculated as the main source of auto-fluorescence. The lignin on the paper exhibits the spatial solid phase dispersion behavior. Molecular simulation proved that heavy metal ions replaced Na + of lignosulfonate. Abstract: Auto-fluorescence of cellulose paper is often considered as an interfering fluorescence, which directly impedes the cellulose paper as a substrate material. This paper creatively explored the composition and properties of auto-fluorescence, and lignosulfonate was primarily speculated as the main source of auto-fluorescence. Surprisingly, its spatial solid phrase dispersion-induced fluorescence enhancement behavior was found. Then, cellulose paper was modified with Mn-doped ZnS quantum dots, and the prepared ratiometric fluorescent paper chip has good performances on morphology, stability, and fluorescence properties. Besides, the paper chip exhibited different fluorescence responses to three heavy metal ions in water sample. The limit of detection for Cd 2+, Hg 2+ and Pb 2+ reached 1.61 nM, 0.01 nM, and 0.02 nM, respectively. In short, the molecular simulation results theoretically proved that heavy metal ions owned substitution affinity with lignosulfonate. Ultimately, this study was the first attempt to utilize paper-based auto-fluorescence, which could better accelerate the development of paper-based chips.